Remote Monitoring of Energy using LoRA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The quantity of electric energy utilised by a home, a business, or an electrically powered device is measured by an electricity metre, also known as an energy meter. Electric meters located at customers' locations are used by electric utilities for billing purposes. These metres are often calibrated in billing units, with the kilowatt hour being the most popular one (kWh).The interface of LoRA-enabled energy metre readings with Arduino nano, Heltec ESP32, and RA-02 LoRA module 433 MHz applications, which have applications where one can enable the data of smart energy metres that can be accessed through long-range areas, is discussed in this paper. A wireless communication technology called LoRA is marketed as a long-range, low-power, low-bit-rate infrastructure for the Internet of Things. End-devices communicate with gateways that are connected to the internet using LoRA over a single wireless hop. These gateways function as transparent bridges that pass messages between these end-devices and a central network server.In addition to being a desirable option for long-distance outside connectivity, LoRA-based Low Power Wide Area Network (LPWAN) Technology is also incredibly practical for use inside of buildings. Additionally, it allows for low-power transmission across a distance of more than 10 kilometres. The sub-GHz radio frequency bands used by LoRA are 433MHz, 868MHz, 915MHz, and 923MHz. In order to access the energy metre reading using our mobile devices, we must first interface the Quasar L&T smart energy meter's RS-485 with a LoRA generic module (consisting of a LoRA module-433MHz coupled to an Arduino Nano on a single board) and a gateway module (Heltec ESP32 LoRA -433 MHz).